Jana Ponętowskiego wierszowana relacja o unii lubelskiej i sejmie 1569 roku - Kroczak, Jerzy (Tematy i Konteksty, 2019)
The union between Kingdom of Poland and Grand Duchy of Lithuania, a legal act with permanent and historically important effects, was signed in Lublin in 1569. Jan Ponętowski (a nobleman, probably a witness of the events) wrote a poetic report on the event entitled Krótki rzeczy polskich sejmowych pamięci godnych komentarz (Short Commentary on Memorable Polish Parliamentary Matters), printed in Cracow in 1569. The paper touches upon what Ponętowski says about the Union and other events in Lublin during the parliament: diplomatic missions, judgments, topics of talks and news from other lands. It also tries to explain why the Union of Lublin (the most important achievement of the parliament) was only marginally described by the author; and also why he only laconically reported the solemn feudal homage of Albert Frederick, the Duke of Prussia, to the Polish king Sigismund II Augustus. The paper compares Ponętowski’s book with old-Polish historiographical descriptions of these matters.